Credit risk management of Southeast Bank Ltd. (Mohammadpur Branch) - Akhter, Syeda Nazia (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.